A multi-component reaction of electron-rich arenes, potassium metabisulfite, aldehydes and aryldiazonium tetrafluoroborates. Issue 7 (3rd February 2021) - Huang, Jiapian; Ding, Feng; Chen, Ziyi; Yang, Gege; Wu, Jie
Abstract : A multi-component reaction of electron-rich arenes, potassium metabisulfite, aldehydes and aryldiazonium tetrafluoroborates under mild conditions is reported, leading to a range of (arylsulfonyl)methylbenzenes in moderate to good yields. Abstract : A multi-component reaction of electron-rich arenes, potassium metabisulfite, aldehydes and aryldiazonium tetrafluoroborates in the presence of formic acid under mild conditions is reported. A range of (arylsulfonyl)methylbenzenes is afforded in moderate to good yields with the formation of multiple new bonds. Under the conditions, this transformation proceeds smoothly with broad substrate scope, and various functional groups are compatible. During the reaction process, excellent chemoselectivity is observed.